(untitled) (Bangladesh Journal of Psychiatry, 2021)
The anxiety scale, developed by Deeba and Begum in 2004 is the most used scale to clinically measure the anxiety in Bangladesh. After ten years, Sarker, Deebaand Begum reviewed the scale in 2018. Since the utility of the scale for everyday clinical work wasdeemed not very prospective, so the scale was examined again on 147 participants (87 clinical and 60 non-clinical participants) from May 2020 to April 2021. The exploratory factor analysis (EFA) suggests a two-factor solution of the short version of revised anxiety scale for Bangladeshis (R AS, B), social factor and physiological factor and yielded 17 items significantly corresponding to the factors. Confirmatory factor analysis was conducted followed by that on those 17 items of the measure for supporting social and physiological factors. Split-half reliability of the scale was found 0.93 (á= 0.01) and the Cronbach-alpha reliability was 0.94 for the measure. The test retest reliability (r=0.45) was also found to be significant (á=0.01). Content validity of the scale was established by strictly following the sequential system model of scale development and by multiple experts’ evaluations on scale items. The depression anxiety stress scale (DASS) 21 was selected as an external criterion to assess the criterion related validity and found to be positive correlated with the present scale (r=0.78). A percentile rank of this scale was determined for the purpose of the clinical usage of the measure; where we had found that scores within 0-30 could be considered as mild anxiety, 31-43 as moderate anxiety, 44-53 as severe anxiety and 54-68 as profound anxiety. The screening norm was found 19.5. Bang J Psychiatry 2021;35(2): 28-35